PERAN PENGANEKARAGAMAN TANAMAN TERHADAP PERKEMBANGAN PEMBANGUNAN PERTANIAN DI INDONESIA ROLE OF CROPS DIVERSIFICATION ON AGRICULTURAL DEVELOPMENT IN INDONESIA - Saparita, Rachmini (Pembangunan Pedesaan, 2005)
The aim of study was to identify the progress of crops diversification representing crops distribution pattern as long as agricultural development had been taking place in Indonesia and to identify the effect of diversification on increasing productivity in order to see its contribution on agricultural sector growth. The result showed that the progress of the diversification was parallel with agricultural development in Indonesia. While agricultural development run progressively, the diversification characterized by index diversification became to expand. The condition indicated that the crops became more competitive. Paddy, sweet potatoes, and cassava were the highest comparative advantages of food crops because of their productivity and index diversification among other food crops. Those three crops were the biggest activator of agricultural transformation in agriculture development in Indonesia. As long as agricultural development occurred in Indonesia, agricultural growth rate was determined dominantly by productivity of land. The sequence of contribution to the growth rate was paddy (17.5%), peanut (17.2%), sweet potatoes (15.0%), cassava (11.6%), soybean (11.6%), and maize (5.4%).